Pengembangan Media Ajar Wallchart pada Mata Pelajaran Matematika Kelas 1 di Sekolah Dasar - Haya, Anabillah Fadya; Khofifah, Indah Nur; Ainia, Vivy Nur; Azahra, Dea Binar; Angelyta, Salsabilla; Istiq’faroh, Nurul; Zahroh, Ulfi Aminatuz (Tumoutou Social Science Journal, 2024)
Learning media is an important component in the teaching and learning process. This media functions as a learning resource that contains learning material and is able to stimulate students’ interest and motivation to learn. So that learning media has a very important role in creating a meaningful learning process and supporting the achievement of educational goals. This study aims to develop and validate wallchart media as a mathematics learning aid in elementary school. The method used is Research and Development (R&D) based on the ADDIE model which consists of five stages: analysis, design, development, implementation, and evaluation. This media is designed to help students understand mathematics concepts in a more visual, interactive, and fun way. Based on the results of the trial research, it shows that the wallchart teaching media fulfils the criteria of valid, practical, and effective. Wallchart can be a learning media that supports students’ learning process optimally.